Integrating Technology in Teaching Mechanics: A Distance Learning Perspective - Taufik, Muhammad; Hikmawati, Hikmawati (Department of Physics Education, Universitas Mataram, 2025)
This study explores the integration of technology in teaching mechanics to undergraduate Physics Education students through Google Meet for synchronous learning and Google Docs for assignment submission. Involving 16 third-semester students, the research measures conceptual understanding using pre-tests and post-tests, evaluates assignment submissions across 12 sessions, and assesses student satisfaction with online learning tools. Results show significant improvement, with average pretest scores of 60 and post-test scores of 86, reflecting a 26-point increase. Assignment scores averaged 84 across all students, and satisfaction levels indicated overall positive experiences with the technology despite connectivity challenges. This study highlights that integrating technology enhances learning outcomes in mechanics education.